ISOLASI MIKROBA TANAH YANG BERPOTENSI MENGHASILKAN ANTIMIKROBA - Ririn Puspadewi; Rina Anugrah; Afif Abdulbasith; Intan Yunita (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2020)
The soil is one of the habitats for microorganisms, in one gram soil there are millions of microorganism. Population microorganism per gram the rich soil of covering bacteria, actinomycetes, fungi, algae and protozoa. Garden having the potential to do exploration of isolation microorganisms. This is because land contains many organic compounds and minerals that is one ecosystem fertile to life and growth microorganisms. Whenever a microorganisms have proven produce substance antimicrobe so organisms of its potential as producer antibiotics. Material research the land, taken from the soil Faculty of Pharmacy Plant Garden of UNJANI, we did dilution and cultivated in a media potato dextrose broth. The isolate from medium broth was cultivating in a media potato dextrose agar, to obtained isolates single. Isolates obtained seen features macroscopic and microscopic. The results obtained isolates isolation two of the four isolates that can give inhibition to Escherichia coli but does not inhibition to Staphylococcus aureus. Keywords: isolation, microbe, soil